?MYCOFLORA OF STORED AND FRESHLY HARVESTED MUSTARD AND RAPESEED GROWN IN PAKISTAN - AHMAD, MANSOOR A; KHAN, BUTOOL A; MASOOD, AHMADUNISA; SHAMSUDDIN, ZUZZER A. (Biological Sciences - PJSIR, 1996)
A large number (1,273) of samples of mustard and rapeseed were collected from 116locations belonging to 38' districts of Pakistan. Eighty nine known varieties were collected from different agricultural research institutes and studied for fungal infections. The dominant genus isolated from freshly harvested crop was Alternaria with 55% frequency of occurrence. In stored seeds,Aspergillus spp.,Alternaria spp. and Penicillium spp. were present in that order. In case of meal and cake, the Aspergillus showed over 50% frequency of occurrence followed by Penicillium whereas. Fusarium spp. and Stemphylium spp. also showed significant dominance in freshly harvested seeds.